Enzyme‐catalysed polymer cross‐linking: Biocatalytic tools for chemical biology, materials science and beyond. Issue 9 (8th July 2020) - Maddock, Rosie M. A.; Pollard, Gregory J.; Moreau, Nicolette G.; Perry, Justin J.; Race, Paul R.
Abstract: Intermolecular cross‐linking is one of the most important techniques that can be used to fundamentally alter the material properties of a polymer. The introduction of covalent bonds between individual polymer chains creates 3D macromolecular assemblies with enhanced mechanical properties and greater chemical or thermal tolerances. In contrast to many chemical cross‐linking reactions, which are the basis of thermoset plastics, enzyme catalysed processes offer a complimentary paradigm for the assembly of cross‐linked polymer networks through their predictability and high levels of control. Additionally, enzyme catalysed reactions offer an inherently 'greener' and more biocompatible approach to covalent bond formation, which could include the use of aqueous solvents, ambient temperatures, and heavy metal‐free reagents. Here, we review recent progress in the development of biocatalytic methods for polymer cross‐linking, with a specific focus on the most promising candidate enzyme classes and their underlying catalytic mechanisms. We also provide exemplars of the use of enzyme catalysed cross‐linking reactions in industrially relevant applications, noting the limitations of these approaches and outlining strategies to mitigate reported deficiencies. Abstract :